Tingkat Literasi Islam Pelaku Penyalahgunaan Narkoba di Kota Bima dan Kabupaten Bima - Syarifatul Mubarak (Universitas Islam Negeri (UIN) Mataram, 2022)
The development of various technological in the era 4.0 does not only have a positive impact on people's lives. It will cause negative things, one of which is drug abuse. One of the areas where cases of drug abuse are rampant is Bima. Data on drug abuse by the age of 15-25 years even reached 63 percent. So that researchers are interested in choosing a theme related to the level of Islamic literacy of drug abusers. This study is a quantitative study with a sample of 25 people and using Islamic literacy instruments to collect related data. The results of the study then showed that the level of Islamic literacy had an average achievement of 29.75 which was in the low category. Where for each aspect, namely the belief aspect by 16% (very low), the ritual and surrender aspect respectively by 34% (low) and the knowledge aspect by 35% (low).